FMR1 Low Zone CGG Repeats: Phenotypic Associations in the Context of Parenting Stress - Mailick, Marsha R.; Hong, Jinkuk; DaWalt, Leann Smith; Greenberg, Jan S.; Movaghar, Arezoo; Baker, Mei Wang; Rathouz, Paul J.; Brilliant, Murray H. (Frontiers in Pediatrics, 2020)
The FMR1 gene on the X chromosome has varying numbers of CGG repeats. The modal number is 30, and expansion to > 200 results in fragile X syndrome, but the copy number extends down to 6. Past research suggests that individuals whose CGGs are in the “low zone” (LZ; defined here as ≤ 25 CGGs) may be more environmentally-reactive than those with normal-range repeats (26-40 CGGs) – a gene x environment interaction. Using a population-based DNA biobank, in our primarily analysis we compared 96 mothers with LZ CGG repeats on both alleles to 280 mothers who had CGG repeats in the normal range. Secondarily, we conducted parallel analyses on fathers. We investigated how parents in these two CGG repeat categories differentially responded to stress, defined as parenting a child with disabilities. Significant gene x environment interactions indicated that LZ mothers who had children with disabilities had greater limitations (in executive functioning, depression, anxiety, daily health symptoms, and balance) than LZ mothers whose children did not have disabilities. In contrast, mothers with normal-range CGG repeats did not differ based on stress exposure. For fathers, a similar pattern was evident for one phenotype only (hand tremors). Although on average LZ CGGs are not associated with compromised functioning, the average masks differential response to the environment.